Diversification and biodiversity dynamics of hot and cold spots. Issue 4 (9th February 2015) - Melián, Carlos J.; Seehausen, Ole; Eguíluz, Víctor M.; Fortuna, Miguel A.; Deiner, Kristy
<x xml:space="preserve">Abstract</x> The determinants that shape the distribution of diversity of life on Earth have been long discussed and many mechanisms underlying its formation have been proposed. Yet connecting the biogeography of hot and cold spots of diversiﬁcation and current biodiversity patterns to the microevolutionary processes remains largely unexplored. Here, we combine a landscape genetics model based on demographic stochasticity with a speciation model that can be interpreted as a model of the evolution of premating incompatibility or assortative mating to map diversiﬁcation rates in a spatial context. We show that landscape structure and the intensity and directionality of gene ﬂow strongly inﬂuence the formation of hot and cold spots and its connection to patterns in species richness. Speciﬁcally, hot and cold spots form in landscapes in which gene ﬂow is suﬃciently strongly structured that the metacommunity nearly breaks up into several disconnected metacommunities. In such a landscape structure, speciation hot spots originate in the center or in the periphery of the landscape depending on whether the direction of gene ﬂow is from the periphery to the center or viceversa, respectively. However, for any given level of gene ﬂow intensity, diversiﬁcation rates are approximately twice higher in the center than in the periphery of the landscape. These results suggest that sinks may form diversiﬁcation hot spots with higher probability than sources, in particular, those sinks surrounded by highly diversiﬁed sources in diﬀerent locations of the landscape. Joining mechanistically microevolutionary and macroevolutionary processes on landscapes present many fascinating challenges and opportunities to connect the biogeography of diversiﬁcation with biodiversity dynamics.